2013
DOI: 10.1051/0004-6361/201220512
|View full text |Cite
|
Sign up to set email alerts
|

The place of the Sun among the Sun-like stars

Abstract: Context. Monitoring of the photometric and chromospheric HK emission data series of stars similar to the Sun in age and average activity level showed that there is an empirical correlation between the average stellar chromospheric activity level and the photometric variability. In general, more active stars show larger photometric variability. Interestingly, the measurements and reconstructions of the solar irradiance show that the Sun is significantly less variable than indicated by the empirical relationship… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…10). Models and measurements indicate that the solar irradiance variability on the 11 year cycle timescale is smaller than given by the Lockwood et al (2007) empirical regression of the stellar variability vs. activity (see, e.g., Knaack et al 2001;Judge et al 2012;Shapiro et al 2013a, and references therein). Because our model is based on SATIRE, which accurately reproduces the measured TSI variability, it is no surprise that it also leads to the same deviation.…”
Section: Photometric Variability Versus Mean Activitymentioning
confidence: 86%
See 3 more Smart Citations
“…10). Models and measurements indicate that the solar irradiance variability on the 11 year cycle timescale is smaller than given by the Lockwood et al (2007) empirical regression of the stellar variability vs. activity (see, e.g., Knaack et al 2001;Judge et al 2012;Shapiro et al 2013a, and references therein). Because our model is based on SATIRE, which accurately reproduces the measured TSI variability, it is no surprise that it also leads to the same deviation.…”
Section: Photometric Variability Versus Mean Activitymentioning
confidence: 86%
“…This approach is starting to attract attention and has already been employed in the literature to constrain solar variability (Preminger et al 2011;Judge et al 2012;Shapiro et al 2013a). The model presented below provides a quantitative basis for this comparison.…”
Section: Solar Irradiance Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that on a long time scale the position of the Sun on the diagram of photometric variability versus CA changers is not constant in time. So Shapiro et al (2013) suggested that the temporal mean solar variability might be in agreement with stellar data.…”
Section: The Place Of the Sun Among The Sun-like Stars With Differentmentioning
confidence: 60%